Graphene-based anisotropic polarization meta-filter. (August 2021) - Zhang, Cheng; Long, Chang; Yin, Sheng; Song, Rong Guo; Zhang, Bo Han; Zhang, Jing Wei; He, Da Ping; Cheng, Qiang
Graphical abstract: Highlights: Graphene film with arbitrary sheet resistance is fabricated and characterized for flexibly design of electronics. A graphene-based anisotropic meta-filter is proposed to select and manipulate the valuable polarization without redundant reflection. The proposed meta-filter shows a wideband characteristic beyond the X band. Abstract: Artificially engineered metamaterials/metasurfaces provide an extraordinary strategy for tailoring the electromagnetic properties of devices, which may break conventional limits in existing polarization filters. Hence, this paper presents an anisotropic graphene-based meta-filter that contains the features of both a phase-gradient metasurface and an electromagnetic absorber, thereby enabling versatile beam behaviors and low reflection loss under orthogonal polarization. In the meantime, our design offers an idealized platform for polarization decomposition and manipulation. Three cases are presented to assess the performance of the proposed meta-filter in the microwave band of interest and to demonstrate its anisotropic nature and polarization-extraction functionality. The corresponding meta-filters are meanwhile characterized by numerical simulation and experimental measurement, the results of which are in good agreement. In addition, the employment of novel graphene films endows the bi-functional meta-filter a promising candidate for future electronic applications in special scenarios calling for excellent environmental resistance and superb flexibility et al.